OPTIMIZATION OF SURGICAL TACTICS IN COMBINATION OF CORONARY HEART DISEASE AND MITRAL INSUFFICIENCY - Ismatov A. A.; Yarbekov R. R.; Teshayev U.Sh.; Muradov M. M.; Akhmedov H. E. (Web of Journals Publishing, 2025)
Coronary heart disease (CHD) and mitral insufficiency (MN) often co-exist, creating significant challenges for surgical treatment. A comprehensive approach that includes differentiated strategies depending on the degree of valve damage and the condition of the coronary arteries can improve the prognosis and quality of life of patients.
Keywords: IHD, mitral insufficiency (MI), coronary arteries.